Association between red cell distribution width-to-albumin ratio and prognostic outcomes in pediatric intensive care unit patients: a retrospective cohort study - Jing, Rui; Yu, Baolong; Xu, Chenchen; Zhao, Ying; Cao, Hongmei; He, Wenhui; Wang, Haili (Frontiers in Pediatrics, 2024)
Objective: This study aimed to assess the association between Red Cell Distribution Width-to-Albumin Ratio (RAR) and the clinical outcomes in Pediatric Intensive Care Unit (PICU) patients.Design: This is a retrospective cohort study.We conducted a retrospective cohort study based on the Pediatric Intensive Care database.The primary outcome was the 28-day mortality rate. Secondary outcomes included the 90-day mortality rate, in-hospital mortality rate, and length of hospital stay. We explored the relationship between RAR and the prognosis of patients in the PICU using multivariate regression and subgroup analysis.Results: A total of 7,075 participants were included in this study. The mean age of the participants was 3.4 ± 3.8 years. Kaplan-Meier survival curves demonstrated that patients with a higher RAR had a higher mortality rate. After adjusting for potential confounding factors, we found that for each unit increase in RAR, the 28-day mortality rate increased by 6% (HR = 1.06, 95% CI: 1.01-1.11, P = 0.015). The high-RAR group (RAR ≥ 4.0) had a significantly increased 28-day mortality rate compared to the low-RAR group (RAR ≤ 3.36) (HR = 1.7, 95% CI: 1.23-2.37, P < 0.001). Similar results were observed for the 90-day and in-hospital mortality rate. No significant interactions were observed in the subgroup analysis.Our study suggests a significant association between RAR and adverse outcomes in PICU patients. A higher RAR is associated with higher 28-day, 90-day, and in-hospital mortality rates.This study extracted data from the Pediatric Intensive Care (PIC) database, a large, open, specialized, and single-center pediatric database (21). The database comprises clinical data from 12,881 pediatric patients with 13,941 hospitalizations in various ICUs at the Children's Hospital, Zhejiang University School of Medicine, China, from 2010 to 2018. The collected information included basic demographic data, diagnoses, laboratory test results, microbiological results, medication records, clinical outcomes, and vital signs during surgical procedures. The project obtained approval from the